O'Reilly Book Club. (O'Reilly Media, Inc., 2023)
Join us for this edition of O'Reilly Book Club with Chip Huyen, author of Designing Machine Learning Systems. You'll learn more about the complex and quickly evolving components of current machine learning systems and how best to ensure your systems are scalable, reliable, and taking advantage of the developing technologies in the field. Ask questions, learn tricks of the trade, listen to stories, and connect with other readers. What you'll learn and how you can apply it Discuss the challenges you're facing and discover opportunities for building machine learning systems for industry Learn tips for developing reliable, scalable, and adaptive machine learning systems for changing environments and business requirements This live course is for you because... You want to go beyond the words on the page and hear directly from the subject matter expert. You're a data scientist, data/machine learning engineer, machine learning architect, or software engineer who is building systems on top of AI models. Recommended follow-up: Read Designing Machine Learning Systems (book) Read Machine Learning Interviews (early release book) Read Machine Learning Design Patterns (book) Watch Designing Machine Learning Systems (Superstream video) Follow AI Superstream: Designing Machine Learning Systems (expert playlist) Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.